THE CONCEPTS OF VIRTUAL COUPLES GROUP INTERVENTIONS (VCGi) MODULE TO IMPROVE MARITAL QUALITY AMONG MARRIED COUPLE - Maziah Mohamed Nasir; Noor Azniza Ishak (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This article presents Virtual Couples Group Interventions (VCGi), which provides knowledge and skill to improve the marital quality among married couples. Virtual couple group intervention can be used as an alternative in delivering counselling services to clients in need. Through this intervention, participants are exposed to improve communication skill, adjustment and intimacy in each session. The content of this intervention has focus on the dimensions of marital quality such as adjustment, communication and adjustment. This module consists six components that focus on marital quality, adjustment, communication, intimacy, conflict management, and restructuring the family or roles. The implementation of this intervention is through a virtual approach that may be applied in counseling sessions, marriage strengthening workshops, guidance groups and marriage educations to couple.